Improving eating disorder care for underserved groups: a lived experience and quality improvement perspective - Alykhan Asaria (Journal of Eating Disorders)
Abstract Improvements to eating disorder (ED) care are urgently needed in the United Kingdom (UK) and around the world. Informed by my lived experiences, independent research, and involvement in the underappreciated field of quality improvement (QI), I have written this article to offer ideas on how to improve individuals' access to and experiences of ED care. As I live in the UK, my lived and QI experiences are of the UK’s National Health Service (NHS). However, much of this article’s content can be applied broadly to healthcare providers around the world, as similar ED care improvements are needed internationally. Furthermore, this commentary is informed by the latest international research. In this paper, I will identify and discuss 12 groups of individuals whom I believe are more likely to be underserved in ED care. The 12 ‘underserved groups’ (USGs) are as follows: [USG. 1] People with longstanding EDs and/or older-age ED sufferers; [USG. 2] Younger children/preadolescents; [USG. 3] People with under-recognised/underappreciated EDs; [USG. 4] People with higher weights; [USG. 5] People with comorbidities; [USG. 6] People with neurodevelopmental conditions (neurodiverse people); [USG. 7] Digitally excluded people; [USG. 8] Socioeconomically and/or sociogeographically disadvantaged people; [USG. 9] Ethnic/racial minorities; [USG. 10] Sexual and gender-diverse people; [USG. 11] Males; [USG. 12] Caregivers/loved ones. ED sufferers/caregivers are also an underserved group as a whole in general mental health care, so broader considerations for improving ED care will be explored in a future publication; these include stigma, research biases, inadequate clinical monitoring and diagnosing, poor-quality treatments, disorganised service transitions, systemic problems/inefficiencies, and underfunding/under-resourcing. Specific recommendations for USGs 1–12 must be considered alongside these and other broader issues. Throughout both articles, I advocate a humanistic care model/approach based on the inexpensive principles of compassion, hope, empathy, appreciation (of identity), and patience (‘CHEAP’).